KLASIFIKASI PENGGUNA LIMA DOMPET DIGITAL TERPOPULER DI INDONESIA DENGAN METODE MCA - Anggraeni Dias Saputri; Ahmad R. Pratama (Fakultas Seni Rupa dan Desain ITB, 2021)
E-wallets have been widely adopted in Indonesian society, providing opportunities for fintech companies to competeon delivering the best service. There has been considerable research conducted on the use of e-wallet services acrossthe globe, however not so many research have provided a comprehensive analysis of the profiles and characteristicsof e-wallet users in Indonesia. This study aims to fill that gap by investigating the profile and characteristics ofusers of the top five e-wallet services in Indonesia based on their popularity, i.e., GoPay, OVO, Dana, LinkAja andShopeePay. This study also aims to understand the differences in user demographic information of each e-wallet.Using the Multiple Corresponding Analysis (MCA) method on the survey data from 409 users of e-wallet services inIndonesia, this study identifies several different profiles of users, i.e., three clusters based on e-wallet ownership andseven clusters based on the most frequently used e-wallet services. The results of this study can help to provide a betterunderstanding of the profiles and characteristics of the e-wallet users in Indonesia, which can be used as inputs to serviceproviders to improve the quality of service they provide to their customers and to reach an even broader audience.